First-Principles Study of Structural and Electronic Properties of Chromium Nitride/Gallium Nitride Multilayer (CrN/GaN) (2013)
In this work we perform first-principles calculations to investigate the structural and electronic properties of the 1x1 CrN/GaN multilayer. The calculations were executed in zincblende and wurtzite phase, since they are the ground states of chromium nitride CrN and gallium nitride GaN, respectively. However, we study the stability of the multilayer in the NaCl phase, in order to predict possible phase transitions. We found that the most favorable phase for the multilayer is the hexagonal wurtzite type, with possibility of passing to the NaCl phase by applying an external pressure. Our calculations indicate that the pressure of transition is 13,5 GPa. From the density of states, we found that the multilayer present a metallic behavior produced by the hybrid orbitals d-Cr and N-p that cross level Fermi.